Synthesis and Antifungal Evaluation of 1,2,4-Triazolo[1,5-α]pyrimidine Bearing 1,2,4-Triazole Heterocycle Derivatives - Chen, W.; Xiang, F.; Fu, J.; Zeng, Q.F.; Zhu, H.L. (Asian Journal of Chemistry, 2010)
In order to search novel fungicides with higher activity, 28 new 1,2,4-triazolo[1,5-α]pyrimidine derivatives bearing 1,2,4-triazole heterocycle were synthesized. Their structures were characterized by 1H NMR spectroscopy, mass spectrometry and elemental analyses. With triadimefon, validamycin and carbendazim as positive controls, the antifungal activities of 28 compounds against Fusarium oxysporum f. sp. vasinfectum, Gibberella sanbinetti, Cercospora beticola Sacc., Physaclospora piricola and Rhizoctonia solani were evaluated. Compound 2-[(5-(2,6- difluorobenzylthio)-4-phenyl-4H-1,2,4-triazol-3-yl)methylthio]-5,7-dimethyl[1,2,4]triazolo[1,5- α]pyrimidine (19) showed potent antifungal activities against G. sanbinetti, C. beticola, P. piricola and R. solani. On the basis of the biological results, structure-activity relationships of these compounds were also discussed.